2010
DOI: 10.1016/j.jasms.2010.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Nanomaterial-based surface-assisted laser desorption/ionization mass spectrometry of peptides and proteins

Abstract: We have investigated six nanomaterials for their applicability as surfaces for the analyses of peptides and proteins using surface-assisted laser desorption/ionization mass spectrometry (SALDI-MS). Gold nanoparticles (NPs) were useful nanomaterials for small analytes (e.g., glutathione); Pt nanosponges and Fe 3 O 4 NPs were efficient nanomaterials for proteins, with an upper detectable mass limit of ca. 25 kDa. Nanomaterials have several advantages over organic matrices, including lower limits of detection for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 20 publications
0
75
0
Order By: Relevance
“…The lack of matrix molecules/ ions in matrix plume results in clean spectral background in low mass spectral region; however, this fails to carry macromolecules into the gas phase. The upper detected mass limits using various NP matrices are generally below 26 kDa for protein samples and 7 kDa for polymers [34,58]. A HgTe NP matrix was reported to increase the upper mass limit for proteins to 150 kDa [59].…”
Section: Npca Maldi Ms Of High Mass Pdmsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of matrix molecules/ ions in matrix plume results in clean spectral background in low mass spectral region; however, this fails to carry macromolecules into the gas phase. The upper detected mass limits using various NP matrices are generally below 26 kDa for protein samples and 7 kDa for polymers [34,58]. A HgTe NP matrix was reported to increase the upper mass limit for proteins to 150 kDa [59].…”
Section: Npca Maldi Ms Of High Mass Pdmsmentioning
confidence: 99%
“…High molecular mass analysis with NP matrices has been particularly problematic [40,58]. The possible cause is that NPs are heavy and surface bound, and thus do not form an abundant matrix plume like organic matrices.…”
Section: Npca Maldi Ms Of High Mass Pdmsmentioning
confidence: 99%
“…Chiang et al studied six different nanomaterials (Au NPs, Fe 3 O 4 NPs, TiO 2 NPs, Se NPs, CdTe quantum dots and Pt nanosponges) for their applicability in the analyses of small analytes, peptides and proteins. 42 Au NPs were reported as the most suitable substrate for small analytes; for larger molecules, the Fe 2 O 3 and Pt nanosponges were demonstrated as the most efficient substrate allowing the detection of molecules up to 25 kDa. To increase the specificity toward an analyte, NP surface modification or conjugation with recognition biomolecules, such as aptamers, can be employed.…”
Section: Selection Of Npsmentioning
confidence: 99%
“…[50]. Shenar et al compared peptide LDI efficiency on supports of pencil lead, porous silica gel, DIOS-chip and NALDI ™ target, and showed that chromashowed that chromaed that chromatography porous silica gel was more attractive than existing reference supports for sensitive peptide detection [51].…”
Section: Nanomaterial-assisted Laser Desorption Ionizationmentioning
confidence: 99%